PELATIHAN KOMUNIKASI SEBAGAI KESIAPAN KERJA SISWA SMK PARIWISATA CITAYAM - Faridah, Faridah; Syafrial, Herry; Nurlina, Nurlina; Yoeliastuti, Yoeliastuti (JURNAL ABDIMAS PLJ, 2025)
This Community Service Program aims to strengthen the communication skills of students at SMK Pariwisata Citayam as part of their preparation for industrial internships and future employment. The training focused on enhancing verbal and nonverbal communication skills, as well as improving students’ confidence in professional situations. The methods used included interactive lectures, question-and-answer sessions, group discussions, and practical activities such as public speaking simulations and job interview practices. The program was conducted face-to-face and involved students from various study programs. The results showed that students demonstrated improved understanding of effective communication principles, increased confidence in speaking, and greater learning motivation. Observations during the program indicated that the training contributed to preparing students mentally for workplace demands. Therefore, this communication training is proven effective in supporting the work readiness of SMK Pariwisata students and is recommended to be implemented continuously for sustainable soft-skill development.